2016
DOI: 10.1162/ling_a_00218
|View full text |Cite
|
Sign up to set email alerts
|

Cyclicity and Connectivity in Nez Perce Relative Clauses

Abstract: This article studies two aspects of movement in relative clauses, focusing on evidence from Nez Perce. First, I argue that relativization involves cyclic Ā -movement, even in monoclausal relatives: the relative operator moves to Spec,CP via an intermediate position in an Ā outer specifier of TP. The core arguments draw on word order, complementizer choice, and a pattern of case attraction for relative pronouns. Ā cyclicity of this type suggests that the TP sister of relative C constitutes a phase-a result whos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 64 publications
2
16
0
Order By: Relevance
“…It follows that themes that raise to ergative (as discussed in the next section) will initially be assigned nominative, and subsequently have their case overwritten. This connects with the proposal for case overwriting discussed in Deal (2016a).…”
Section: Diagnosing Unaccusativitysupporting
confidence: 79%
See 1 more Smart Citation
“…It follows that themes that raise to ergative (as discussed in the next section) will initially be assigned nominative, and subsequently have their case overwritten. This connects with the proposal for case overwriting discussed in Deal (2016a).…”
Section: Diagnosing Unaccusativitysupporting
confidence: 79%
“…by Appl), or as a morphological default, reflecting the absence of any case assignment (cp.Schütze 2001, Preminger andKornfilt 2015). Previous research has indicated that both analyses are required for certain portions of Nez Perce grammar: nominative on intransitive subjects involves a [NOM] feature, whereas nominative on leftperipheral DPs in the hanging-topic left dislocation (HTLD) construction is a morphological default(Deal, 2016a). The difference in the status of nominative is revealed by case attraction of relative pronouns.…”
mentioning
confidence: 99%
“…We set aside the question of whether the phasehood of syntactic heads might be sensitive to other syntactic factors(Gallego and Uriagereka 2007;Bošković 2014;Deal 2016), although such proposals do make phonological predictions in the context of a theory like CBP. 7 In the glossing above we depart from the regular glossing convention for Moro, where the 'finite' vowel is typically glossed RTC for root clause.…”
mentioning
confidence: 99%
“…In (27), we see this for a relative clause island. (On the islandhood of relative clauses in Nez Perce, see Deal (2016a).) The judgment can also be replicated in other island configurations, e.g.…”
Section: The Composition Of Prolepsis Clausesmentioning
confidence: 91%
“…The data in this paper come from fieldwork conducted with two speakers, Bessie Scott and Florene Davis, on the Nez Perce Reservation in Lapwai, Idaho, over an approximately ten-year period. Descriptions of various aspects of Nez Perce grammar may be found in Aoki 1970, Rude 1985, 1992, 1999, Crook 1999, and Deal 2010a,b, 2011, 2013, 2016a,b,c, 2017a,b, 2018, To appear, among other sources. Here, I will focus selectively on aspects of the language which prove especially relevant for understanding the composition of its attitude reports.…”
Section: Nez Perce: Some Backgroundmentioning
confidence: 99%